Assessment of technical compliances to landowners guides in forest roads of Oluwa forest reserve Ondo State Nigeria (2012)
Assessment of the various types of hazard exposed to by logging crews in a Nigerian Forest Reserve was carried in this study. The study site was the Ondo State Afforestation Project Forest road construction appears to be the most expensive single investment in forest operations and designing forest road to specification is a complex engineering problem involving economic, environmental and social factors. The study was carried out to assess the technical compliances to recommended land owners guide to building forest access road in a forest estate in Nigeria. The study was carried out at Ondo State Afforestation Project (OSAP) Headquarters, South West Nigeria. Data collected for the study involved collation of road parameters such as road length, carriage way, drain depth and width, and comparative analysis of these with standard road parameters. Data collected were then subjected to descriptive and inferential statistics. Result showed that the road width in all the locations ranged from 12.23m and 7.15 m with a mean of 9.42m as against the recommended 11.00m. The width of the carriage way ranged from 4.4m to 8.76m while the drain depth ranged from 0.51m and 1.20m in all the selected locations. The difference in the observed width and the standard width was significant at 5% level of probability. Both the observed carriage way width and drain depth were significantly different from the recommended standards. OSAP access roads therefore, fall short of the recommended standard landowners’ guide to building forest access roads.